CHEMOPROTECTIVE EFFECT OF EDIBLE GASTROPOD, XANCUS PYRUM AND ITS USEFULNESS IN THE AMELIORATION OF CISPLATIN-INDUCED TOXICITY - Jayaprakash, Bindhu; Renitta, Emilin; Renitta, Emilin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The main purpose of this study was to evaluate chemoprotective activities of methanolic extracts of an edible gastropod (Xancus pyrum) in cisplatin-induced immunosuppressed mice. Methods: Cisplatin (100 mg/kg, intraperitoneally [IP]) induced immunosuppressed mice were treated with a methanolic extract of X. pyrum (0.5 mg/dose/animal/IP) for a period of 10 days. The effect of the extract on lymphoid organ weight, bone marrow cellularity (BMC), alpha esterase activity, and on enzyme levels such as serum glutamic oxaloacetic transaminase, serum glutamic pyruvic transaminase, urea, and creatinine was estimated to identify the chemoprotective activity of X. pyrum. Results: Administration of X. pyrum extract in cisplatin-treated mice, found to enhance the BMC and alpha-esterase positive cells, which were drastically reduced in cisplatin alone treated control animals suggests that cisplatin-induced myelosuppression was reversed or inhibited by X. pyrum extract administration possibly through its chemoprotective activity. Conclusion: Cisplatin and its metabolites can bind to DNA, causing damage that may result in chromosome breaks, micronucleus formation and cell death. Administration of X. pyrum extract in cisplatin-treated mice, found to enhance the BMC and alpha-esterase positive cells, which were drastically reduced in cisplatin alone treated control animals suggests that cisplatin-induced myelosuppression was reversed or inhibited by X. pyrum extract administration possibly through its chemoprotective activity.